COMPARATIVE REVIEW OF REGULATORY FRAMEWORK OF VIRTUAL CURRENCY (CRYPTOCURRENCY) IN SELECTED COUNTRIES - Kasprzyk, Marcin (Review of European and Comparative Law, 2018)
In the era of rapid technological progress, the legislators of individual countries face the challenge of submitting new technological phenomena to the legal framework. The business operation in the field of virtual currencies (cryptocurrencies), widely, in the financial technology sector (hereinafter referred to in as “fintech”), create a chance to attract investors and develop the economy. On the other hand, the same might be misused for illegal purposes, such as, in particular, money laundering or financing of terrorism. This study provides for an overview of the legal regulations of selected states in the field of virtual currencies (cryptocurrencies). Although, presented laws and regulations herein are in favour of the cryptocurrencies, the scope of implemented acts varies significantly.